THE EVALUATION OF BIOLOGY TEACHING USING INVERTEBRATE TAXONOMY TEXTBOOK - Rahmadina Rahmadina; Linda Eriri (Universitas Islam Negeri Ar-Raniry, 2021)
The purpose of this research is to produce a research book based on invertebrate taxonomy in Biology Lectures using Borg & Gall based development methods combined with Dick & Carey's learning in the Stages of development, namely: preliminary studies, planning, product draft development, product validation tests by experts, lecturers and peer reviewer, product revision, product trial, product revision. Data collection uses a questionnaire with descriptive data analysis techniques. Based on the results of research that has been developed, it is considered very good and feasible to be used as a textbook with an average of 102.5 (81.3%) by the validation team of material experts and learning designs, as well as lecturers and peer reviewers with an average of 72 (82,91 %), The results of trials by students individually, small groups and limited field of textbooks Invertebrate Taxonomy is very good and feasible to be developed with an average value of 730.6 (86.6%).